Improving the Interpersonal Intelligence of the Students with Intellectual Disability through the BCCT Approach - Yuana Maulidia; Sopingi Sopingi; Usep Kustiawan (Department of Special Education, 2018)
Children with intellectual disability have a slow social development. Such as the interpersonal aspects of intelligence. The learning approach that can be used is Beyond Centers And Circle Time (BCCT) approach. The purpose is to describe interpersonal intelligence before and after being given the treatment as well as analyze the effect of the approach Beyond Centers And Circle Time approach interpersonal intelligence intellectual disability. The method used was Quasi-Experiment with Time Series Design and analysis with Wilcoxon test hypothesis. Based on the data analysis, It can be concluded that the BCCT approach effect significantly for the interpersonal intelligence of the students with intellectual disability.